2017
DOI: 10.1016/j.ijplas.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Continuum approach for modeling fatigue in amorphous glassy polymers. Applications to the investigation of damage-ratcheting interaction in polycarbonate

Abstract: In this article, we propose an approach suitable for modeling isothermal fatigue in amorphous polymers. The theory is formulated in a rate form within continuum mechanics framework without the need to measure damage changes per loading cycles. Using the approach, contribution of ratcheting to fatigue of polycarbonate (PC) was investigated and the results were compared to previous experimental observations. When subjected to uniaxial stress-controlled cyclic loadings, ratcheting deformation apparently occurs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…the mean strain grows as the applied load varies between its maximum and minimum values, cf. Jiang et al (2015); Holopainen et al (2017); Kang and Kan (2017). A significant initial increase of ratcheting deformation is due to the great mean stress level used.…”
Section: Load-controlmentioning
confidence: 99%
See 1 more Smart Citation
“…the mean strain grows as the applied load varies between its maximum and minimum values, cf. Jiang et al (2015); Holopainen et al (2017); Kang and Kan (2017). A significant initial increase of ratcheting deformation is due to the great mean stress level used.…”
Section: Load-controlmentioning
confidence: 99%
“…proposing a spinW vep which is algorithmically consistent, i.e. it becomes finally skew-symmetric at the end of the integration step, Holopainen and Wallin (2012); Engqvist et al (2016); Holopainen et al (2017). Then, supposing the current deformation gradient F is known (as it does in standard finite-element implementations), the variables needed to be solve become:…”
Section: Concluding Remarks and Further Research Avenuesmentioning
confidence: 99%
“…Yu et al (2017) showed that their model for an ultra-high molecular weight polyethylene is accurate under low-cycle loadings. Considering the longer fatigue lives and ratcheting of polymers, the focus has been on uniaxial cyclic loadings, Kim and Lu (2008); Xi et al (2015); Wang et al (2016); Kanters et al (2016); Hughes et al (2017); Holopainen et al (2017); Holopainen and Barriere (2018); Barriere et al (2019); Krairi et al (2019). The experimentation and models for PC proposed in James et al (2013); Ravi Chandran (2016) are studied under uniaxial cyclic loadings and are implemented to detect crack growth in tiny zones (not applied at component level) to define long-term fatigue lives.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, due to the more and more extensive applications of polymeric materials in engineering, many researchers began to pay attention to the study of cyclic deformation behavior of these materials; for example, Chen et al [7] investigated the influence of humidity on cyclic deformation behavior and cyclic heat generation of polyamide-6 polymer. e results show that the change of humidity will not change the inherent cyclic softening/ hardening features of the material but obviously affects the degree of cyclic softening/hardening of the material; Liu et al [8] discussed the effects of stress cycling on the physical aging of polycarbonate polymer; Holopainen et al [9] proposed a model to simulate the ratchetting and fatigue interaction behavior of polycarbonate polymer in the framework of continuum mechanics; Hughes et al [10] experimentally studied the fatigue behavior of polycarbonate polymers and proposed a multistage fatigue model to evaluate the crack evolution; Zhang et al [11] proposed a method to accelerate ratchetting testing based on the time-temperature equivalence principle and verified the effectiveness of the proposed method with the uniaxial ratchetting test of polycarbonate polymer; Li et al [12] studied the effect of cyclic deformation on the mechanical properties of polycarbonate polymer. e results reveal that, during the initiation of fatigue damage, the fracture toughness of the material decreases with the increasing number of cyclic loadings significantly, while the yield strength is almost unaffected; Fang et al [13] conducted cyclic deformation experiments on polycarbonate (PC) and polycarbonate/acrylonitrile-butadiene-styrene (PC/ABS) and discussed the effects of cyclic loading on the uniaxial tensile properties of the two kinds of materials.…”
Section: Introductionmentioning
confidence: 99%